Change-O: a toolkit for analyzing large-scale B cell immunoglobulin repertoire sequencing data - Gupta, Namita T.; Vander Heiden, Jason A.; Uduman, Mohamed; Gadala-Maria, Daniel; Yaari, Gur; Kleinstein, Steven H. (Bioinformatics, 2015)
Advances in high-throughput sequencing technologies now allow for large-scale characterization of B cell immunoglobulin (Ig) repertoires. The high germline and somatic diversity of the Ig repertoire presents challenges for biologically meaningful analysis, which requires specialized computational methods. We have developed a suite of utilities, Change-O, which provides tools for advanced analyses of large-scale Ig repertoire sequencing data. Change-O includes tools for determining the complete set of Ig variable region gene segment alleles carried by an individual (including novel alleles), partitioning of Ig sequences into clonal populations, creating lineage trees, inferring somatic hypermutation targeting models, measuring repertoire diversity, quantifying selection pressure, and calculating sequence chemical properties. All Change-O tools utilize a common data format, which enables the seamless integration of multiple analyses into a single workflow. Availability and implementation: Change-O is freely available for non-commercial use and may be downloaded from http://clip.med.yale.edu/changeo. Contact:  steven.kleinstein@yale.edu